Jaringan Komunikasi dalam Pengembangan Program Masjid Nusantara - Febriyanto Febriyanto; Muhammad Nasha Prasetyo; Mohammad Zidan Asyawa; Muhammad Rizki Dwi Yuliyanto; Nani Nurani Muksin (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
he Role of Communication Networks in Supporting the Development of the Masjid Nusantara Program, a strategic initiative focused on the construction and empowerment of mosques across various regions in Indonesia. This study employs a descriptive qualitative approach using Social Network Analysis (SNA), with data collected through in-depth interviews with key informants from the Masjid Nusantara Foundation. The findings reveal that digital communication channels such as social media, WhatsApp, email, and the official website play a vital role in promoting the program, building public engagement, and mobilizing financial support. Internal coordination is carried out regularly and systematically through digital platforms, with local volunteers serving as the key communication bridges in the field. The established communication network involves various actors, including the central team, volunteers, donors, community leaders, and external partners, who collaborate in a participatory and coordinated manner.